Skrining Fitokimia Kualitatif Ekstrak Etanol 96% dan H-Heksana Kulit Batang Bakau Lindur (Bruguiera gymnorrhiza) - Ismunanto, Aziza Regina Kinasih; Kurniawati, Evi; Putri, Giska Tri; Susianti, Susianti (Medula, 2025)
Lindur mangrove plants (Bruguiera gymnorrhiza) are known to contain secondary metabolite compounds which function as antibacterials. These secondary metabolite compounds include alkaloids, flavonoids, tannins, phenols, saponins, terpenoids and steroids. The design of this research was experimental, carried out to determine and compare the phytochemical components contained in 96% ethanol extract and n-hexane of Bruguiera gymnorrhiza mangrove bark. Bruguiera gymnorrhiza mangrove bark was taken at KPH Gunung Balak, East Lampung, then 4.5 kg of wet mangrove bark was obtained and dried for 7 days, then the extract was made using the maceration method for 3x24 hours using 2 types of solvents, namely 96% ethanol and n-hexane with a ratio of 1:10 between simplicia and solvent. Thick extracts were obtained from the two types of solvents which were then carried out qualitative phytochemical tests.  The results of this study showed that 96% ethanol extract and n-hexane of Bruguiera gymnorrhiza mangrove bark positively contained secondary metabolite compounds. The 96% ethanol extract of Bruguiera gymnorrhiza mangrove bark contains all types of secondary metabolite compounds, namely alkaloids, flavonoids, tannins, phenols, saponins, terpenoids and steroids, while the n-hexane extract contains secondary metabolite compounds, namely alkaloids, flavonoids, tannins, phenols, terpenoids, steroid but does not contain saponins. The conclusion of this research is that the 96% ethanol extract of Bruguiera gymnorrhiza mangrove bark contains more secondary metabolite compounds than the n-hexane extract of Bruguiera gymnorrhiza mangrove bark.